Matlab based modeling and simulink package for DC-DC boost convertor to enhance learning process of power electronics - Asad, Muhammad Mujtaba (2014)
In this study, DC-DC boost converter Matlab Simulink Package has been developed and tested for the enhancement of learning process within academic course of power electronics. Respondent for this research were chosen randomly from Faculty of Electrical & Electronic Engineering, Tun Hussein Onn University of Malaysia. Aim of this study is to figure out and see the effectiveness of DC-DC boost convertors Simulink package for the enhancement of learning process of Power electronic course. A Preresearch statistical analysis based on the response of concerned students acquired through a relative questioner is employed to affirm the need of this simulation package. Analysis for this study has been verified by using Statistical Package for Social Science (SPSS) Version 20.0 software. Afterwards, a simulation package as required has been developed accordingly to test and illustrate the operation of DC-DC boost convertor using open-loop, Proportional integral derivative (PID) controller and Fuzzy logic controller topologies. Finally, a post-research questioner was also floated through same respondent population in order to evaluate and assess the effect and significance of the designed simulation package. It was observed through the statistical analysis of the afore mentioned post research questioner that, the use of simulation based package regarding the enhancement of learning proved to have a significant effect. Expect this study findings will be one of the catalysts in strengthening improve the instructional methods by using simulation software’s in Power electronics and engineering courses.